VD_FINDINFO HC / 2014 / 812 vom 20. Oktober 2014 - VD Tribunal cantonal (2014)
MESURE PROVISIONNELLE, ACTION EN DIVORCE, TRANSACTION JUDICIAIRE, ASSISTANCE JUDICIAIRE | 241 al. 2 CPC (CH), 241 al. 3 CPC (CH)